2007
DOI: 10.1111/j.1600-0609.2007.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma/leukaemia transformed from a precursor B cell: clinical and molecular aspects

Abstract: Burkitt lymphoma/leukaemia (BL/L) is a heterogeneous disease with respect to epidemiological patterns and cell origin. The occurrence of BL/L with an immature phenotype raises the question whether this phenotype might be a consequence of early B-cell transformation or, alternatively, a secondary feature of transformed, mature B cells. It also poses important clinical questions regarding diagnosis and therapeutic procedures. Here we describe the case of a 4-yr-old child with BL/L and FAB L3 morphology, with phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…patients whose karyotype data and immunophenotyping data diagnostic for BCP-ALL were complete and available were analyzed 2,4,12,[14][15][16][17][18][19][20][21] ( Table 3). The blast immunophenotypes reported in these publications were similar to those of our patients, except for positivity [23][24][25] By contrast, the standard treatment for ALL is long-term chemotherapy that comprises three phases: induction, consolidation, and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…patients whose karyotype data and immunophenotyping data diagnostic for BCP-ALL were complete and available were analyzed 2,4,12,[14][15][16][17][18][19][20][21] ( Table 3). The blast immunophenotypes reported in these publications were similar to those of our patients, except for positivity [23][24][25] By contrast, the standard treatment for ALL is long-term chemotherapy that comprises three phases: induction, consolidation, and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…8 Among cases with a precursor B-cell immunophenotype, [9][10][11][12] only one TdT-negative cases has been reported. 8 Among cases with a precursor B-cell immunophenotype, [9][10][11][12] only one TdT-negative cases has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data regarding optimal management of patients with a precursor B cell phenotype BL with IGH-MYC rearrangement. 9,10 However, Hassan et al 10 reported a patient with a precursor B cell phenotype BL who was treated with a modified ALL-BFM 95 protocol and was alive and in hematological and clinical remission. 11,12 Of the four adult patients with treatment and treatment course available in the reports, treatments were the Hyper-CVAD protocol (two patients), high-risk B-ALL protocol (one patient), and R-CHOP (one patient).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations